Naming of Some Selected Macro Settlement Places in Gojjam - Walelign Melak; Desalegn Hagos; Mulugeta Tarekegn (Journal of Ethiopian Studies)
This study aims to investigate the naming systems, meanings, and languages of place names, contributing to sociolinguistic knowledge for the people. The study employs a descriptive qualitative research design. In-depth interviews and document consultations were used as tools for data collection. The raw data of place names were taken from the zone and woreda agriculture offices. Informants, who included experts in the Culture and Tourism Office, elderly people, and clergymen, were selected purposively. The data analysis showed that some selected macro settlement place names are bestowed in single, paired, and /Ɂnnə-/-based personal name systems. These personal name-based place name systems are indexations of acclaimed individuals and founders who established their territories in their names. On the other hand, name systems are signs of territorial administrative integration, reflecting the psychology of acclaimed individuals, people’s experiences, and human circumstances in life. Moreover, some macro settlement place names have water, gender, land features, time, and religion-based name systems. Semantically, these settlement place names have referential and connotative meanings. Despite the language of the names, some were bestowed in Amharic and Ge’ez, while others were named in a Ge᾽ez-Amharic hybrid. Moreover, a few of the names were in Afaan Oromo and Hebrew. Essentially, place names were manifestations of geospatial identity, human coincidence, religious affiliation, and the natural characteristics of the landscape in various socio-cultural dimensions.